PARA PIHAK DAN PERANNYA DALAM PEMBANGUNAN KPH MODEL DI TANAH PAPUA - Irma Yeny (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
The reasons for poor performance of forest management unit (FMU) area establishment is the very minimum role of the parties in its planning. The aims of research were to analyze parties of the stakeholders and their roles in the implementation of FMU Model in Papua based on their perception. Data were obtained by interview and literature study, then analyzed by stakeholders analysis and their role quantitatively and descriptively. The results showed that local government through the Ministry of Forestry in provincial and regency levels were the main and important stakeholders in establishing FMU Model in Papua. In this perspective, the main parties have important roles in the preparation, planning, implementation and monitoring. The role of local government as the main actor showed that FMU establishment in Papua was implemented with the perspective and orientation on the local government. In that perspective, the perception and interaction of local government institutions become very dominant and play decisive role in realizing the institution of FMU. Therefore, the paradigm shift from government to governance that reduces government role and increases the role of community could not be applied in the establishment process of FMU in Papua.